IMPLEMENTASI PEMBELAJARAN BIOLOGI BAGI ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH LUAR BIASA BAGIAN B (TUNARUNGU) SMALB DHARMA WANITA KOTA BOGOR - Wulandari Wulandari; Suci Siti Lathifah; Oding Sunardi (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2021)
This research is a qualitative research with descriptive analytic method. The purpose of this study was to describe an analyze learning at SMALB Dharma Wanita Kota Bogor. This research was carried out from February 2019 to Juli 2019 with several informan namely Biology Teacher 1, Principal, Biology Teacher 2, Parents Of Students, Students and Curriculum. This research was conducted with direct contact with the subject of research foun in the field and obtained two types of data, namely primary data derived from interviews and observations, as well as secondary data derived from study documentation, based on data analysis, biology learning in to 3 processes, bamely planning, implementation and evaluation. Biology learning planning at SMALB Dharma Wanita, namely the teacher holding a work meeting ( in house training) discusses the completeness of the administration of the teacher and strategies or methods that will be used by the class. The implementation of biology learning at SMALB Dharma Wanita consists of introductory, core and concluding activities. Evaluation of learning in SMALB Dharma Wanita consists of cognitive, affektive and psychomotor.